2021
DOI: 10.1098/rspa.2020.0717
|View full text |Cite
|
Sign up to set email alerts
|

On non-autonomous differential-difference AKP, BKP and CKP equations

Abstract: Based on the direct linearization framework of the discrete Kadomtsev–Petviashvili-type equations presented in the work of Fu & Nijhoff (Fu W, Nijhoff FW. 2017 Direct linearizing transform for three-dimensional discrete integrable systems: the lattice AKP, BKP and CKP equations. Proc. R. Soc. A 473 , 20160915 ( doi:10.1098/rspa.2016.0915 )), six novel non-autonomous differential-difference equations are established, including three in the AKP clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Multiplying this equation by (1 + 𝛀𝑪 𝑛 ) −1 from the right, we end up with (34b) in virtue of (24). Equations (34a) and (34c) are proven similarly.…”
Section: Closed-form Nonlinear Equationsmentioning
confidence: 90%
“…Multiplying this equation by (1 + 𝛀𝑪 𝑛 ) −1 from the right, we end up with (34b) in virtue of (24). Equations (34a) and (34c) are proven similarly.…”
Section: Closed-form Nonlinear Equationsmentioning
confidence: 90%
“…Therefore by Lemma 7 and spectral representation of q in (17), one can at last prove ( 31) is correct for m. Now let us discuss the expression of g 1 (t, z) by free Bosons, which is given in the proposition below.…”
Section: The Darboux Transformation Of the Ckp Hierarchy Via Free Bosonsmentioning
confidence: 93%
“…The hyperdetermantal relations (2.7.2) were introduced as integrable systems of recurrence relations on lattices by Kashaev [22], who showed that the star triangle relations satisfied by Boltzmann weights for the Ising model imply these for a suitably defined τ -function on the Z 3 integer lattice. They were studied subsequently by Schief and others [30,2,20,21], as discrete analogs of the CKP hierarchy.…”
Section: 3)mentioning
confidence: 99%
“…and substituting eqs. (3.6.42a) -(3.6.42d) into (3.6.43) gives the form of the discrete CKP relations studied in [20,21].…”
Section: Hyperdeterminantal Relations In Infinite Dimensionsmentioning
confidence: 99%